2020
DOI: 10.1021/acs.jpclett.0c00482
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Intersystem Crossing in Isolated Ag29(BDT)123– Probed by Time-Resolved Pump–Probe Photoelectron Spectroscopy

Abstract: The photophysics of the isolated trianion Ag 29 (BDT) 12 3− (BDT = benzenedithiolate), a ligand-protected cluster comprising BDT-based ligands, terminating a shell of silver thiolates and a core of silver atoms, was studied in the gas phase by femtosecond time-resolved, pump−probe photoelectron spectroscopy. UV excitation at 490 nm populates one or more singlet excited states with significant charge transfer (CT) character in which electron density is shifted from shell to core. These CT states relax on an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…To rationally correlate the experimentally observed CCS and the corresponding probable Cu exchange positions in the Ag 29 system, extensive density functional theory (DFT) calculations were carried out. Initially, the structure of Ag 29 (BDT) 12 3– was optimized using the BP-86 functional and def2-SVP basis set as implemented in the recent version of Turbomole with a starting structure based on Bakr et al After removal of the phosphines and energy minimization under constrained symmetry, a CCS value was calculated using the trajectory method as implemented in the IMoS-software (details in the Experimental Section in the Supporting Information). , In the case of N 2 as a drift gas, the charge distribution needs to be considered, therefore a natural population analysis (NPA) analysis was run after the structures had converged.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To rationally correlate the experimentally observed CCS and the corresponding probable Cu exchange positions in the Ag 29 system, extensive density functional theory (DFT) calculations were carried out. Initially, the structure of Ag 29 (BDT) 12 3– was optimized using the BP-86 functional and def2-SVP basis set as implemented in the recent version of Turbomole with a starting structure based on Bakr et al After removal of the phosphines and energy minimization under constrained symmetry, a CCS value was calculated using the trajectory method as implemented in the IMoS-software (details in the Experimental Section in the Supporting Information). , In the case of N 2 as a drift gas, the charge distribution needs to be considered, therefore a natural population analysis (NPA) analysis was run after the structures had converged.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Veenstra demonstrated by pump-probe PES on [Ag 29 (BDT) 12 ] 3-(BDT = 1,3- Please do not adjust margins Please do not adjust margins C 6 H 4 S 2 ) using femtosecond lasers that the long-lived triplet state is populated via ultrafast intersystem crossing from ligand-to-Ag 13 core charge transfer state. 131 Unexpectedly, PES on [M 25 (PET) 18 ] − (M = Au, Ag) revealed that thermionic emission (TE) of a slow electron dominates over direct photodetachment upon photoirradiation at 266 nm. 128 Johnson established high-resolution UV-visible absorption spectroscopy at cryogenic temperature in the gas phase.…”
Section: Laser-based Spectroscopiesmentioning
confidence: 99%
“…The exact origin of the PL is difficult to identify because of the presence of multiple emission sites in the clusters, such as the metal core and surface staple, [7][8][9][10][11][12] as well as the contribution of electronic states with different spin multiplicities (i.e., excited singlet and triplet states) to these emission sites. 7,[13][14][15] Therefore, it would be desirable to determine the rate constants and quantum yields of all radiative and non-radiative processes involving the excited singlet and triplet states of the cluster, so that the complex behavior of the excited-state relaxation processes of the clusters can be accurately understood.…”
Section: Introductionmentioning
confidence: 99%
“…, excited singlet and triplet states) to these emission sites. 7,13–15 Therefore, it would be desirable to determine the rate constants and quantum yields of all radiative and non-radiative processes involving the excited singlet and triplet states of the cluster, so that the complex behavior of the excited-state relaxation processes of the clusters can be accurately understood.…”
Section: Introductionmentioning
confidence: 99%